Assessment of the actual nutrition of rural adolescents of the Irkutsk region because of revision of the norms of physiological needs for energy and nutrients - L. V. Rychkova; A. V. Pogodina; T. A. Astakhova; L. N. Lebedeva (Acta Biomedica Scientifica, 2024)
Background. The rational nutrition of the child population is given great medical importance as a factor in preserving the health and development of the child. A complete and balanced diet in terms of the content of basic nutrients ensures the normal growth and development of the child’s body.The aim. To analyze of the actual nutrition of adolescents living in rural areas of the Irkutsk region.Materials and methods. The study involved 69 rural adolescents aged 11–17 years (34 boys, 35 girls). The actual nutrition was studied by the method of 24-hour nutrition reproduction. The energy value of the diet was determined, the nature of the provision of the diet with basic macro- and microelements was studied. The obtained values were compared with the norms of  physiological needs for energy and nutrients in 2008 and 2021.Results. The analysis of actual nutrition revealed deviations from the principles of  healthy nutrition: insufficient energy value of the diet, deficiency of proteins and  fats. The diet of  adolescents was characterized by an insufficient content of the main groups of macro- and micronutrients – vitamins A, C and D, essential trace elements, and a deficiency of dietary fiber. The diet of adolescents was characterized by increased sodium intake. The calculated ratio of proteins, fats, carbohydrates indicated a carbohydrate type of diet.Conclusion. Despite the great attention to the problem of balanced nutrition of adolescents, the question of the impact of nutrition on the health of a teenager, considering the regional factor, remains open. Recommendations for the development of a regional program for the organization of proper nutrition for school-age children are of great practical importance.